Review of ALERT based on cryptography method (International Journal of Engineering and Computer Science, 2014)
Mobile Ad Hoc Networks (MANETs) make use of advanced network routing protocols that categorize the notes and manage the communication of packets. ALERT (Anonymous Location - Based Efficient Routing Protocol) has remained highly efficient in terms of efficiency and maintenance of consistency. ALERT protocol is now applied to the packet communication to achieve secured encryption and decryption of data. This can also help in achieving a high degree of security within the network. ALERT based on cryptography proves to be reliable for multipath transmission in networks of varied complexities.